2009
DOI: 10.1007/s10680-009-9184-z
|View full text |Cite
|
Sign up to set email alerts
|

Low Fertility and Long-Run Growth in an Economy with a Large Public Sector

Abstract: Recently it has been suggested that low fertility countries may be caught in a trap that is hard to get out of. One important mechanism in such a trap would be social interaction and its effect on the ideal family size. Such social interaction mechanisms are hard to capture in formal models, therefore we use an agent-based simulation model to investigate the issue. In our experimental setup a stable growth and population pa th is calibrated to Swedish data and using the Swedish social policy setup. The model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These findings are in line with empirical studies (Gauthier and Hatzius 1997;Björklund 2006;Gauthier 2007;Feyrer, Sacerdote, and Stern 2008;Egger and Radulescu 2012) and microsimulation models (Kalb and Thoresen 2010). Social networks and social effects are also found to affect fertility, which coincides with empirical results (Bühler and Philipov 2005;Philipov, Spéder, and Billari 2006;Balbo and Mills 2011) and with simulation models (Zamac, Hallberg, and Lindh 2010). Moreover, proportional policies contribute more to the indirect effect (increase in intended fertility) while the contribution of fixed policies to the direct effect (reduction of the gap between intended fertility and completed cohort fertility) and indirect effect are approximately equal.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with empirical studies (Gauthier and Hatzius 1997;Björklund 2006;Gauthier 2007;Feyrer, Sacerdote, and Stern 2008;Egger and Radulescu 2012) and microsimulation models (Kalb and Thoresen 2010). Social networks and social effects are also found to affect fertility, which coincides with empirical results (Bühler and Philipov 2005;Philipov, Spéder, and Billari 2006;Balbo and Mills 2011) and with simulation models (Zamac, Hallberg, and Lindh 2010). Moreover, proportional policies contribute more to the indirect effect (increase in intended fertility) while the contribution of fixed policies to the direct effect (reduction of the gap between intended fertility and completed cohort fertility) and indirect effect are approximately equal.…”
Section: Discussionsupporting
confidence: 89%
“…With an eye to better informing policy development, contributors Zamac et al (2010) consider the mechanisms by which countries may become caught in (and escape from) a low fertility trap and its economic effects. Using an agent-based simulation model that draws on data and policy from Sweden, they show that an increase in the relative costs of children can cause a fertility trap to occur only if social norms start adapting to lower fertility.…”
Section: Contributions To the Special Issuementioning
confidence: 99%
“…Most developed countries are faced with so-called fertility crisis as birth rates have dropped below the replacement fertility rate. Studies regarding low fertility rates pointed that total fertility rate (TFR) should be maintained upper 2.1 to secure stable population [1][2][3]. In line with declining of global birth rates, Korean National Statistical Office (KOSTAT) reported that the TFR of Korea is 1.2 in 2014 [4].…”
Section: Introductionmentioning
confidence: 99%